2017
DOI: 10.1186/s13054-017-1855-2
|View full text |Cite
|
Sign up to set email alerts
|

Functional evaluation of sublingual microcirculation indicates successful weaning from VA-ECMO in cardiogenic shock

Abstract: BackgroundVeno-arterial extracorporeal membrane oxygenation (VA-ECMO) is increasingly adopted for the treatment of cardiogenic shock (CS). However, a marker of successful weaning remains largely unknown. Our hypothesis was that successful weaning is associated with sustained microcirculatory function during ECMO flow reduction. Therefore, we sought to test the usefulness of microcirculatory imaging in the same sublingual spot, using incident dark field (IDF) imaging in assessing successful weaning from VA-ECMO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 40 publications
3
44
0
2
Order By: Relevance
“…Few studies aimed at identifying criteria to predict which patients can be successfully weaned from ECMO, using the same methodology ( Table 1) (13)(14)(15)(18)(19)(20). They assessed prospectively and daily clinical, biological and/or echo parameters until death, weaning or bridge to long-term assist-device or heart transplantation.…”
Section: Which Factors Can Help To Predict Successful Weaning From Vamentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies aimed at identifying criteria to predict which patients can be successfully weaned from ECMO, using the same methodology ( Table 1) (13)(14)(15)(18)(19)(20). They assessed prospectively and daily clinical, biological and/or echo parameters until death, weaning or bridge to long-term assist-device or heart transplantation.…”
Section: Which Factors Can Help To Predict Successful Weaning From Vamentioning
confidence: 99%
“…Akin et al recently reported in a study on 13 patients that the assessment of the sublingual microcirculation functional parameters, such as the total vessel density and perfused vessel density, may be of worth alongside weaning from VA ECMO (19). Patients who were not weaned from VA ECMO had clear deterioration in total small and large vessel densities.…”
Section: Microcirculation Parametersmentioning
confidence: 99%
“…However, to limit biases due to the absence of randomization, we used a multivariate logistic regression model with a propensity score analysis. Although several definitions of VA-ECMO weaning success have been proposed [11, 29, 30], we adopted the definition used in the recent study by Distelmeier et al [10]. Aortic velocity–time integral and left ventricular ejection fraction were not collected in the control group.…”
Section: Limitationsmentioning
confidence: 99%
“…Inhaled nitric oxide improves RV function by reducing pulmonary vascular resistance [ 32 ]. Total vessel density and perfused vessel density monitoring of sublingual microcirculation have been found to have a good association with aortic VTI, LVEF parameters during ECMO wean [ 33 ].…”
Section: Post-cardiotomy Va-ecmomentioning
confidence: 99%